Wheat rust surveillance in South Africa – A molecular approach - Botma Visser; Cornel M. Bender; Tarekegn Terefe; Zacharias A. Pretorius; Willem H.P. Boshoff (South African Journal of Botany, 2025)

Pathogenicity of Puccinia porri on Allium in South Africa - Willem H. P. Boshoff; Botma Visser; Cornel M. Bender; Zacharias A. Pretorius (Australasian Plant Pathology, 2024)
Allium crops are commonly grown in South Africa and harvested as either fresh produce for the domestic and export markets or as seed. Apart from occasional outbreaks on garlic, rust is problematic as a cosmetic disease with unappealing uredinia regularly observed on freshly packed produce of bunching onion and leek in supermarkets. Spore morphology and phylogenetic analysis of five rust samples collected from A. fistulosum (bunching onion) confirmed the causal organism as Puccinia porri . Garlic and bunching onion varieties were mostly susceptible to P. porri , whereas leek varieties were either susceptible or segregating in their response, with bulb onions being resistant. Microscopy of early infection structures showed appressorium formation, stomatal penetration, and a substomatal structure which differentiated into infection hyphae and haustorium mother cells. At microscopy level differences in host response became visible from 48 h post-inoculation onwards with prehaustorial and early hypersensitivity observed as resistance mechanisms in onions.

Dietary B vitamin and methionine intake and MTHFR C677T genotype on risk of colorectal tumors in Lynch syndrome: the GEOLynch cohort study - Audrey Y. Jung; Fränzel J. B. van Duijnhoven; Fokko M. Nagengast; Akke Botma; Renate C. Heine-Bröring; Jan H. Kleibeuker; Hans F. A. Vasen; Jan L. Harryvan; Renate M. Winkels; Ellen Kampman (Cancer Causes & Control, 2014)

Do lifestyle factors influence colorectal cancer risk in Lynch syndrome? - Fränzel J. B. van Duijnhoven; Akke Botma; Renate Winkels; Fokko M. Nagengast; Hans F. A. Vasen; Ellen Kampman (Familial Cancer, 2013)

Microsatellite analysis of selected Puccinia triticina races in South Africa - Botma Visser; Liezel Herselman; Cornelia M. Bender; Zacharias A. Pretorius (Australasian Plant Pathology, 2012)

Characterization of two new Puccinia graminis f. sp. tritici races within the Ug99 lineage in South Africa - Botma Visser; Liezel Herselman; Robert F. Park; Haydar Karaoglu; Cornelia M. Bender; Zacharias A. Pretorius (Euphytica, 2011)

Cloning, expression, and promoter analysis of hepatic lipase derived from human hyperplastic adrenals - Gert-Jan Botma; Mirjam Heuveling; Jos M. J. Lamers; Hans Jansen; Adrie J. M. Verhoeven (Cell Biochemistry and Biophysics, 2007)

Hemifacial microsomia: progress in understanding the genetic basis of a complex malformation syndrome - D. Kelberman; J. Tyson; D. Chandler; A. McInerney; J. Slee; D. Albert; A. Aymat; M. Botma; M. Calvert; J. Goldblatt; E. Haan; N. Laing; et al. (Human Genetics, 2001)